Student Guidance and Counseling based on Expert System Using Certainty Factor Method - Ismail; Novaliyan, Alvin Rangga; Fernandes, Atman Lucky; Hendro Wahyudiono, Pratiwi; Olva, Maria; Suganda, Afdal; Iksan, Nur; Yani, Achmad; Panessai, Ismail Yusuf (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Setiap kampus atau perguruan tinggi memiliki satu layanan yang disebut bimbingan dan konseling. Peran ini dipegang oleh dosen penasehat akademik. Beban kerja dosen penasehat akademik menjadi tinggi ketika rasio jumlah dosen dan mahasiswa rendah. Untuk meringankan beban kerja dosen penasehat akademik maka dibuat sebuah sistem pakar yang dapat memudahkan mahasiswa dan dosen penasehat akademik dalam mengatasi permasalahan yang ada. Pembangunan sitem pakar ini menggunakan metode pengembangan Expert System Development Life Cycle (ESDLC). Aplikasi yang dibangunkan kemudian diujikan kepada mahasiswa Teknik Informatika di Universitas Ibnu Sina. Pengujian meliputi uji Black Box. Dari evaluasi pengguna diperoleh hasil bahwa sistem pakar yang dibangunkan dapat digunakan untuk menangani masalah-masalah seperti yang telah disimpan dalam daftar data masalah dan solusi. Tampilan estetika sistem harus diperbaiki agar pengguna tertarik untuk menggunakannya. Beberapa pengguna mengusulkan elemen multimedia dimasukkan dalam tampilan sistem pakar yang dibangunkan agar tampilannya lebih menarik. Student Guidance and Counseling based on Expert System Using Certainty Factor Method Abstract: Every campus or college has one service called guidance and counseling. This role is held by the academic advisory lecturer. The workload of academic advisory lecturers becomes high when the ratio of the number of lecturers to students is low. To ease the workload of academic advisory lecturers, an expert system is made that can facilitate students and academic advisory lecturers in overcoming existing problems. The development of this expert system uses the Expert System Development Life Cycle (ESDLC) development method. The application that was developed was then tested on Informatics Engineering students at Ibn Sina University. Tests include the Black Box tests. From the evaluation of the user obtained the results that the developed expert system can be used to deal with problems such as those that have been stored in the list of problem data and solutions. The aesthetic appearance of the system must be improved in order for users to be interested in using it. Some users suggest multimedia elements be included in the developed expert system view to make it look more attractive. Keywords: Guidance and Counseling, Certanty Factor, Expert Systems.